Economic Exposure During the Covid - 19 - rengga madya pranata (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to see the economic exposure of various industrial sector manufacturing companies listed on the Indonesian stock exchange during the Covid-19 pandemic in the time span used is Q4 2019 to Q3 2020. With the number of samples used were 30 companies that had data. which will be used. Testing in this study uses multiple regression to see the influence of factors that can affect economic exposure. From the results obtained in this study. Show that the model used can be used to measure factors that help increase or decrease economic exposure, although if partially company size cannot be a determinant of economic exposure during this pandemic, only liquidity and market to book ratio can only be determinants of economic exposure. part of the company during the Covid-19 pandemic.